GEOLOGICAL OBJECTS OF GLOBAL SIGNIFICANCE IN EUROPEAN RUSSIA - Lapo A.V.; Davydov V.I.; Pashkevich N.G.; Petrov V.V.; Vdovets M.S. (My University, 1997)
Geological heritage, as part of natural heritage, includes the in situ located geological reference objects (sites) visualising geological phenomena with high information potential. Forty objects of geological heritage of worldwide significance in the territory of European Russia are briefly described. From the viewpoint of the specific geological structure of the territory, the most numerous are the stratigraphic, paleontological, geohistorical, and geological mining objects. The stratigraphic type objects are represented mainly by strato-types and key sections of different Upper Paleozoic units, whereas the paleontological type objects include localites with fossil remains of Permian and Triassic tetrapods.
Keywords: Paleozoic; Permian; Triassic; Paleozoic::Permian; Палеозой::Пермская; Paleozoic; Мезозой::Триасовая; Mesozoic::Triassic; Палеозой